2018 EULAR recommendations for physical activity in people with inflammatory arthritis and osteoarthritis - DURUÖZ, MEHMET TUNCAY (BMJ PUBLISHING GROUP, 2018)
Regular physical activity (PA) is increasingly promoted for people with rheumatic and musculoskeletal diseases as well as the general population. We evaluated if the public health recommendations for PA are applicable for people with inflammatory arthritis (iA

Rheumatoid Arthritis and Spondyloarthritis) and osteoarthritis (hip/knee OA) in order to develop evidence-based recommendations for advice and guidance on PA in clinical practice. The EULAR standardised operating procedures for the development of recommendations were followed. A task force (TF) (including rheumatologists, other medical specialists and physicians, health professionals, patient-representatives, methodologists) from 16 countries met twice. In the first TF meeting, 13 research questions to support a systematic literature review (SLR) were identified and defined. In the second meeting, the SLR evidence was presented and discussed before the recommendations, research agenda and education agenda were formulated. The TF developed and agreed on four overarching principles and 10 recommendations for PA in people with iA and OA. The mean level of agreement between the TF members ranged between 9.8 and 8.8. Given the evidence for its effectiveness, feasibility and safety, PA is advocated as integral part of standard care throughout the course of these diseases. Finally, the TF agreed on related research and education agendas. Evidence and expert opinion inform these recommendations to provide guidance in the development, conduct and evaluation of PA-interventions and promotion in people with iA and OA. It is advised that these recommendations should be implemented considering individual needs and national health systems.
Keywords: HOME-BASED EXERCISE; QUALITY-OF-LIFE; RHEUMATOID-ARTHRITIS; KNEE OSTEOARTHRITIS; ANKYLOSING-SPONDYLITIS; HIP OSTEOARTHRITIS; AEROBIC EXERCISE; OLDER-ADULTS; RANDOMIZED-TRIAL; DISEASE-ACTIVITY